Method for manufacturing antireflection film

By forming antireflection films with specific protective film properties and continuous in-line measurement, the method enhances detection accuracy of reflected and transmitted light, addressing the challenges of film instability and discoloration in existing antireflection film manufacturing.

JP2024177916AActive Publication Date: 2024-12-24NITTO DENKO CORP

Patent Information

Application Number
JP2023096320
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-06-12
Publication Date
2024-12-24
Estimated Expiration
2043-06-12

AI Technical Summary

Technical Problem

Existing methods for manufacturing antireflection films struggle with inaccurate detection of reflected and transmitted light characteristics during in-line inspection, particularly when variations in film formation conditions lead to discoloration and instability in the antireflection layer, especially when using reactive sputtering methods.

Method used

A method involving the formation of an antireflection layer on a transparent film base material with a protective film having specific haze and surface roughness values, allowing for continuous in-line measurement of reflected and transmitted light, and adjusting film-forming conditions based on these measurements to maintain accuracy.

Benefits of technology

Improves the detection accuracy of reflected and transmitted light characteristics during in-line inspection, ensuring consistent film quality and reducing discoloration, even with reactive sputtering methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024177916000001_ABST
    Figure 2024177916000001_ABST
Patent Text Reader

Abstract

To provide a method for manufacturing an antireflection film that can improve accuracy in detecting reflection light and transmission light in an in-line inspection.SOLUTION: A method for manufacturing an antireflection film 100 comprises: a step S1 of preparing a laminate 10 having a transparent film base material 11 and a protection film 12 adhered separably on a first main surface 11a side of the transparent film base material 11; a step S2 of forming an antireflection layer 101 composed of thin films having two or more layers on a second main surface 11b side of the transparent film base material 11; and a step S3 of, after forming at least one layer constituting the antireflection layer 101, irradiating the layer with visible light and detecting reflection light therefrom and transmission light therethrough. The step S2 and the step S3 are continuously executed while conveying unidirectionally the laminate 10. An internal haze value of the protection film 12 is 4.0% or less.SELECTED DRAWING: Figure 3
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an anti-reflection film. [Background technology]

[0002] An anti-reflection film is disposed on the viewing side of an image display device such as a liquid crystal display or an organic EL display for the purposes of preventing deterioration in image quality due to reflection of external light, improving contrast, etc. The anti-reflection film has an anti-reflection layer made of a laminate of multiple thin films with different refractive indices on a transparent film substrate.

[0003] The anti-reflection layer reduces the reflectance of visible light by utilizing the multiple reflection interference of a thin film. Therefore, if the refractive index or thickness of the thin film fluctuates, the reflected light characteristics such as the reflectance and the hue of the reflected light change. Even if the film formation conditions of the thin film are strictly controlled and kept constant in the formation of the anti-reflection layer, the film thickness, refractive index, etc. may fluctuate due to the variation in the characteristics of the raw materials, the change over time in the film formation environment, etc.

[0004] In film manufacturing, in-line measurements are performed during the manufacturing process, and the measurement results are fed back to the previous process to maintain a constant film quality. For example, in Patent Document 1, in-line inspection in the manufacturing process of anti-reflection film is performed by measuring the reflected light characteristics in-line, and feeding back the measurement results to the thin film deposition conditions.

[0005] In general, anti-reflection films are designed so that the visible light reflectance of the surface on which the anti-reflection layer is formed is 1% or less, whereas the visible light reflectance (rear surface reflectance) of the rear surface side of the transparent film substrate (the interface between the transparent film substrate and air) is about 4%. In offline inspection after the formation of the anti-reflection layer, the influence of rear surface reflection can be eliminated and the reflected light characteristics of the front surface side can be measured. On the other hand, most of the reflected light detected in in-line inspection during the manufacturing process of anti-reflection films is reflected light from the rear surface, and even if the characteristics of the reflected light from the surface on which the anti-reflection layer is formed change, the reflected light detected hardly changes at all. Therefore, in general, it is not easy to accurately measure the reflected light characteristics from the surface on which the anti-reflection layer is formed in-line.

[0006] In response to this, the technology described in Patent Document 1 forms an anti-reflection layer on a laminate having a light-diffusing adhesive layer, thereby reducing back surface reflection and improving the detection accuracy of reflected light in in-line inspection. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2016 / 021733 Summary of the Invention [Problem to be solved by the invention]

[0008] On the other hand, when the antireflective layer is continuously formed, the antireflective layer may become discolored due to fluctuations in the film formation conditions, etc. In particular, when the antireflective layer is formed by a reactive sputtering method, it is difficult to stably maintain the transition region between the metal region and the oxide region, and therefore the antireflective layer is likely to become discolored.

[0009] One method for detecting the coloring of an anti-reflection layer by in-line inspection is to measure the transmitted light characteristics of the anti-reflection layer and feed back the measurement results to the thin film deposition conditions. However, it is difficult to improve the detection accuracy of transmitted light in in-line inspection only with the technique described in Patent Document 1.

[0010] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a method for manufacturing an antireflection film that can improve the detection accuracy of reflected light and transmitted light in in-line inspection. [Means for solving the problem]

[0011] <Aspects of the present invention> The present invention includes the following aspects.

[0012] [1] A step S1 of preparing a laminate having a transparent film substrate and a protective film peelably attached to a first main surface side of the transparent film substrate; A step S2 of forming an anti-reflection layer consisting of two or more thin films on the second main surface side of the transparent film substrate; and a step S3 of depositing at least one layer constituting the anti-reflection layer, irradiating the layer with visible light, and detecting reflected light and transmitted light, The steps S2 and S3 are continuously performed while the laminate is transported in one direction, The internal haze value of the protective film is 4.0% or less, The method for producing an anti-reflection film, wherein the surface haze value of the main surface of the protective film opposite to the transparent film substrate side is 6.0% or more and 50.0% or less.

[0013] [2] The method for producing an anti-reflection film described in [1] above, wherein the surface haze value of the main surface of the protective film opposite the transparent film substrate side minus the surface haze value of the main surface of the protective film facing the transparent film substrate side is 5.0% or more.

[0014] [3] A step S1 of preparing a laminate having a transparent film substrate and a protective film peelably attached to a first main surface side of the transparent film substrate; A step S2 of forming an anti-reflection layer consisting of two or more thin films on the second main surface side of the transparent film substrate; and a step S3 of depositing at least one layer constituting the anti-reflection layer, irradiating the layer with visible light, and detecting reflected light and transmitted light, The steps S2 and S3 are continuously performed while the laminate is transported in one direction, The internal haze value of the protective film is 4.0% or less, The method for producing an antireflection film, wherein the root mean square slope Sdq of the main surface of the protective film opposite to the transparent film substrate is 0.10 or more and 0.50 or less.

[0015] [4] The method for manufacturing an antireflection film described in [3], wherein the root-mean-square slope Sdq of the main surface of the protective film opposite the transparent film substrate side minus the root-mean-square slope Sdq of the main surface of the protective film facing the transparent film substrate is 0.05 or more.

[0016] [5] The method for producing an antireflection film according to any one of [1] to [4] above, wherein in the step S2, the antireflection layer is formed by a reactive sputtering method.

[0017] [6] The method for producing an antireflection film according to any one of [1] to [5], wherein in step S3, after all layers constituting the antireflection layer are formed, the antireflection layer is irradiated with visible light, and the reflected light and transmitted light are detected.

[0018] [7] The method for producing an antireflection film according to any one of [1] to [6] above, wherein deposition conditions for the antireflection layer in the step S2 are adjusted depending on detection results of the reflected light and the transmitted light in the step S3.

[0019] [8] The method for producing an antireflection film according to any one of [1] to [7] above, further comprising, after step S3, step S4 of peeling the protective film from the transparent film substrate.

[0020] [9] The transparent film substrate comprises a transparent film and a hard coat layer provided on a first main surface side of the transparent film; The method for producing an antireflection film according to any one of the above [1] to [8], wherein in the laminate, the protective film is attached to a second main surface side of the transparent film.

[0021]

[10] The method further includes a step S5 of forming a primer layer on the second main surface side of the transparent film substrate before the step S2, The method for producing an antireflection film according to any one of [1] to [9] above, wherein in the step S2, the antireflection layer is formed on a main surface of the primer layer opposite to the transparent film substrate. Effect of the Invention

[0022] According to the present invention, a method for producing an antireflection film capable of improving the detection accuracy of reflected light and transmitted light in in-line inspection can be provided. [Brief description of the drawings]

[0023] [Figure 1] FIG. 1 is a cross-sectional view showing an example of a laminate having a transparent film substrate and a protective film. [Diagram 2] FIG. 2 is a schematic diagram illustrating an example of a film forming apparatus for an antireflection layer. [Diagram 3] 1A, 1B and 1C are cross-sectional views illustrating steps in an example of a process for forming an antireflection layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0024] Preferred embodiments of the present invention will be described in detail below, but the present invention is not limited thereto. In addition, all academic and patent documents described in this specification are incorporated herein by reference.

[0025] First, the terms used in this specification will be explained. The "refractive index" is the refractive index for light with a wavelength of 550 nm in an atmosphere at a temperature of 23°C. The "principal surface" of a layered product (more specifically, a transparent film substrate, a transparent film, a hard coat layer, a primer layer, an anti-reflection layer, a protective film, a substrate layer, an adhesive layer, a laminate, etc.) refers to a surface perpendicular to the thickness direction of the layered product. The "first principal surface" of a layered product means one of the two principal surfaces of the layered product. The "second principal surface" of a layered product means the principal surface opposite to the first principal surface side of the layered product.

[0026] Unless otherwise specified, the numerical value for the "thickness (film thickness)" of a layered material is the arithmetic average of 10 measured values ​​obtained by observing a cross section of the layered material cut in the thickness direction with an electron microscope, randomly selecting 10 measurement points from the cross-sectional image, and measuring the thickness of the selected 10 measurement points.

[0027] The "root mean square slope Sdq" is a parameter of the surface shape measured in accordance with ISO 25178, and indicates the degree of slope of the protrusions present on the surface. The "arithmetic mean height Sa (surface roughness Sa)" is a parameter of the surface shape measured in accordance with ISO 25178, and indicates the average of the absolute values ​​of the differences in height of each point with respect to the average plane of the surface. The "root mean square height Sq" is a parameter of the surface shape measured in accordance with ISO 25178, and corresponds to the standard deviation of the height from the average plane of the surface. The specific measurement methods of the root mean square slope Sdq, the arithmetic mean height Sa, and the root mean square height Sq are all the same as or similar to the methods described in the examples below.

[0028] The term "bombardment treatment" refers to a surface treatment in which the surface of a transparent film substrate is subjected to plasma treatment while introducing a specific gas (rare gas, oxygen gas, etc.).

[0029] Unless otherwise specified, the number-average primary particle diameter of particles is the number-average value of the circle-equivalent diameters (Heywood diameter: diameter of a circle having the same area as the projected area of ​​a primary particle) of 100 primary particles measured using a scanning electron microscope and image processing software (e.g., "ImageJ" manufactured by the National Institutes of Health, USA).

[0030] The unit of flow rate "sccm (Standard Cubic Centimeter per Minute)" is the unit of flow rate under standard conditions (temperature: 0°C, pressure: 101.3 kPa), which is "mL / min."

[0031] The "parallel light transmittance" is calculated by measuring the total light transmittance and the diffuse transmittance based on the formula "parallel light transmittance = total light transmittance - diffuse transmittance". The total light transmittance and diffuse transmittance are measured using a haze meter according to the method described in JIS K7105 (now discontinued) (ISO 13468-2:1999).

[0032] Hereinafter, the compound and its derivatives may be collectively referred to by adding "based" after the compound name. In addition, when the compound name is followed by "based" to represent the name of a polymer, it means that the repeating unit of the polymer is derived from the compound or its derivative, unless otherwise specified. In addition, acrylic and methacrylic may be collectively referred to as "(meth)acrylic".

[0033] Unless otherwise specified, the components and functional groups exemplified in this specification may be used alone or in combination of two or more kinds.

[0034] The drawings referred to in the following description are intended to illustrate each component in a schematic manner for ease of understanding, and the size, number, shape, etc. of each component shown in the drawings may differ from the actual size, number, shape, etc., for convenience of drawing. Also, for convenience of explanation, in the drawings described later, the same components as those in the drawings described earlier may be given the same reference numerals, and explanations thereof may be omitted.

[0035] <Method of manufacturing anti-reflection film> The first manufacturing method of the anti-reflection film according to the present embodiment (hereinafter, sometimes referred to as the "first manufacturing method") includes steps S1, S2, and S3. In step S1, a laminate having a transparent film substrate and a protective film peelably attached to the first main surface side of the transparent film substrate is prepared. In step S2, an anti-reflection layer consisting of two or more thin films is formed on the second main surface side of the transparent film substrate. In step S3, after forming at least one layer constituting the anti-reflection layer, the layer is irradiated with visible light, and the reflected light and transmitted light are detected. Steps S2 and S3 are performed continuously while transporting the laminate in one direction. The internal haze value of the protective film used in the first manufacturing method is 4.0% or less. The surface haze value of the main surface opposite to the transparent film substrate side of the protective film used in the first manufacturing method is 6.0% or more and 50.0% or less.

[0036] The second manufacturing method of the anti-reflection film according to the present embodiment (hereinafter, sometimes referred to as the "second manufacturing method") includes steps S1, S2, and S3. In step S1, a laminate having a transparent film substrate and a protective film peelably attached to the first main surface side of the transparent film substrate is prepared. In step S2, an anti-reflection layer consisting of two or more thin films is formed on the second main surface side of the transparent film substrate. In step S3, after forming at least one layer constituting the anti-reflection layer, the layer is irradiated with visible light, and the reflected light and transmitted light are detected. Steps S2 and S3 are performed continuously while transporting the laminate in one direction. The internal haze value of the protective film used in the second manufacturing method is 4.0% or less. The root mean square slope Sdq of the main surface opposite to the transparent film substrate side of the protective film used in the second manufacturing method is 0.10 or more and 0.50 or less.

[0037] The method for measuring the "internal haze value" is the same as or similar to the method for measuring the internal haze value of the protective films P1 to P3 described later in the Examples (specifically, the method for measuring the internal haze value of the protective films P1 to P3). The method for measuring the "surface haze value (external haze value)" is the same as or similar to the method for measuring the surface haze value of the protective films P1 to P3 described later in the Examples (specifically, the method for measuring the surface haze value of the protective films P1 to P3).

[0038] Hereinafter, when there is no need to distinguish between them, each of the first and second manufacturing methods will be referred to as "this manufacturing method." In addition, the "main surface of the protective film opposite the transparent film substrate" may be simply referred to as the "rear surface." In addition, the "main surface of the protective film facing the transparent film substrate" may be simply referred to as the "adhesive surface."

[0039] Hereinafter, step S1 may be referred to as a "laminate preparation step", step S2 may be referred to as an "anti-reflection layer formation step", and step S3 may be referred to as an "in-line measurement step".

[0040] According to the present manufacturing method, since the above-mentioned configuration is provided, it is possible to improve the detection accuracy of reflected light and transmitted light in in-line inspection. The reason for this is presumed to be as follows.

[0041] In this manufacturing method, the anti-reflection layer is formed in a state where a protective film with "a rear surface haze value of 6.0% or more" or "a rear surface root mean square slope Sdq of 0.10 or more" is attached to a transparent film substrate, so that light incident from the anti-reflection layer side tends to be easily scattered on the rear surface (rear surface) of the protective film. As a result, the amount of light (rear surface reflectance) reflected on the rear surface (more specifically, the reflected light reflected on the rear surface and detected by the light detection unit) is reduced, so that this manufacturing method can improve the detection accuracy of the reflected light from the anti-reflection layer-formed surface in in-line inspection.

[0042] In addition, in this manufacturing method, the anti-reflection layer is formed in a state where a protective film having a "surface haze value of the rear surface of 50.0% or less" or a "root mean square slope Sdq of the rear surface of 0.50 or less" and an "internal haze value of 4.0% or less" is attached to a transparent film substrate. Therefore, according to this manufacturing method, it is possible to increase the proportion of parallel components of light that enters from the anti-reflection layer side and exits from the rear surface (increase parallel light transmittance). Therefore, according to this manufacturing method, it is possible to improve the detection accuracy of light (transmitted light) that passes through the anti-reflection layer and exits from the rear surface during in-line inspection.

[0043] In the present manufacturing method, in order to further increase the detection accuracy of transmitted light, the internal haze value of the protective film is preferably 3.5% or less, and more preferably 3.0% or less. In addition, in the present manufacturing method, in order to further increase the detection accuracy of reflected light, the internal haze value of the protective film is preferably 0.5% or more, and more preferably 1.0% or more.

[0044] In the first manufacturing method, in order to further increase the detection accuracy of reflected light, the surface haze value of the rear surface of the protective film is preferably 6.1% or more, and more preferably 6.2% or more. In the first manufacturing method, in order to further increase the detection accuracy of transmitted light, the surface haze value of the rear surface of the protective film is preferably 45.0% or less, and more preferably 43.0% or less.

[0045] In the second manufacturing method, in order to further increase the detection accuracy of reflected light, the root mean square slope Sdq of the back surface of the protective film is preferably 0.11 or more, and more preferably 0.12 or more. In the second manufacturing method, in order to further increase the detection accuracy of transmitted light, the root mean square slope Sdq of the back surface of the protective film is preferably 0.45 or less, more preferably 0.40 or less, and even more preferably 0.35 or less.

[0046] Hereinafter, the details of the method for producing an antireflection film according to this embodiment (the present production method) will be described with reference to the drawings as appropriate.

[0047] [Laminate preparation process] The laminate preparation step is a step of preparing a laminate having a transparent film substrate and a protective film peelably attached to a first main surface side of the transparent film substrate. First, the laminate will be described with reference to Fig. 1. Fig. 1 is a cross-sectional view showing an example of the laminate.

[0048] 1 includes a transparent film substrate 11 and a protective film 12 releasably attached to a first main surface 11a side of the transparent film substrate 11. An antireflection layer 101 (see FIG. 3C), which will be described later, is formed on a second main surface 11b of the transparent film substrate 11.

[0049] In the example shown in FIG. 1, the transparent film substrate 11 includes a transparent film 13 and a hard coat layer 14 provided on the first main surface 13a side of the transparent film 13. In addition, in the example shown in FIG. 1, the protective film 12 includes a base layer 15 and an adhesive layer 16 laminated on the transparent film substrate 11 side of the base layer 15. In addition, the protective film 12 is attached to the second main surface 13b side of the transparent film 13. In other words, the second main surface 13b of the transparent film 13 is attached to the adhesive surface 12b of the protective film 12. In the example shown in FIG. 1, the first main surface 11a of the transparent film substrate 11 and the second main surface 13b of the transparent film 13 are the same surface.

[0050] In order to further increase the detection accuracy of transmitted light, the total light transmittance (JIS K 7375-2008) of the protective film 12 is preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more.

[0051] In the example shown in Fig. 1, the transparent film substrate has a hard coat layer, but the transparent film substrate usable in the present invention is not limited to the above example. For example, the transparent film substrate usable in the present invention does not need to have a hard coat layer. When the transparent film substrate does not have a hard coat layer, for example, a transparent film (transparent film 13 in the example shown in Fig. 1) can be used as the transparent film substrate.

[0052] In this manufacturing method, the internal haze value of the protective film 12 is 4.0% or less. In the first manufacturing method, the surface haze value of the back surface 12a of the protective film 12 is 6.0% or more and 50.0% or less. In the second manufacturing method, the root-mean-square slope Sdq of the back surface 12a of the protective film 12 is 0.10 or more and 0.50 or less.

[0053] In the first manufacturing method, in order to further improve the detection accuracy of reflected light and transmitted light, the value obtained by subtracting the surface haze value of the adhesive surface 12b of the protective film 12 from the surface haze value of the back surface 12a of the protective film 12 is preferably 5.0% or more, and more preferably 5.5% or more. In the first manufacturing method, the upper limit of the value obtained by subtracting the surface haze value of the adhesive surface 12b of the protective film 12 from the surface haze value of the back surface 12a of the protective film 12 is not particularly limited, and is, for example, 40.0% or less.

[0054] In the second manufacturing method, in order to further improve the detection accuracy of reflected light and transmitted light, the value obtained by subtracting the root-mean-square slope Sdq of the adhesive surface 12b of the protective film 12 from the root-mean-square slope Sdq of the back surface 12a of the protective film 12 is preferably 0.05 or more, and more preferably 0.07 or more. In the second manufacturing method, the upper limit of the value obtained by subtracting the root-mean-square slope Sdq of the adhesive surface 12b of the protective film 12 from the root-mean-square slope Sdq of the back surface 12a of the protective film 12 is not particularly limited, and is, for example, 0.30 or less.

[0055] In the second manufacturing method, in order to further improve the detection accuracy of the reflected light and the transmitted light, the arithmetic mean height Sa of the back surface 12a of the protective film 12 is preferably 0.05 μm or more and 0.20 μm or less, and more preferably 0.06 μm or more and 0.18 μm or less. In addition, in the second manufacturing method, in order to further improve the detection accuracy of the reflected light and the transmitted light, the value obtained by subtracting the arithmetic mean height Sa of the adhesive surface 12b of the protective film 12 from the arithmetic mean height Sa of the back surface 12a of the protective film 12 is preferably 0.03 μm or more, and more preferably 0.04 μm or more. In the second manufacturing method, the upper limit of the value obtained by subtracting the arithmetic mean height Sa of the adhesive surface 12b of the protective film 12 from the arithmetic mean height Sa of the back surface 12a of the protective film 12 is not particularly limited, and is, for example, 0.20 μm or less.

[0056] In the second manufacturing method, in order to further improve the detection accuracy of the reflected light and the transmitted light, the root mean square height Sq of the back surface 12a of the protective film 12 is preferably 0.05 μm or more and 0.30 μm or less, and more preferably 0.07 μm or more and 0.25 μm or less. In addition, in order to further improve the detection accuracy of the reflected light and the transmitted light in the second manufacturing method, the value obtained by subtracting the root mean square height Sq of the adhesive surface 12b of the protective film 12 from the root mean square height Sq of the back surface 12a of the protective film 12 is preferably 0.04 μm or more, and more preferably 0.05 μm or more. In the second manufacturing method, the upper limit of the value obtained by subtracting the root mean square height Sq of the adhesive surface 12b of the protective film 12 from the root mean square height Sq of the back surface 12a of the protective film 12 is not particularly limited, and is, for example, 0.25 μm or less.

[0057] The internal haze value of the protective film 12 can be adjusted, for example, by changing at least one of the particle content in the protective film 12 and the particle diameter of the particles in the protective film 12. In order to easily adjust the internal haze value of the protective film 12 to 4.0% or less, the particle content in the protective film 12 is preferably 0.1% by weight or less, and it is more preferable that the protective film 12 does not substantially contain particles.

[0058] The root mean square slope Sdq, arithmetic mean height Sa and root mean square height Sq of the surface of the protective film 12, and the surface haze value of the protective film 12 can be adjusted, for example, by changing the uneven shape of the surface of the protective film 12. The uneven shape of the surface of the protective film 12 is formed, for example, by molding the protective film 12 using a roll molding machine equipped with a molding roll having an uneven surface. When a molding roll having an uneven surface is used, the uneven shape of the molding roll surface is transferred to the surface of the protective film 12 (for example, the back surface 12a of the protective film 12).

[0059] The laminate preparation step may be a step of preparing a commercially available laminate 10, or may be a step of adhering the transparent film substrate 11 and the protective film 12. The method of adhering the transparent film substrate 11 and the protective film 12 is not particularly limited, and an example of such a method includes using a roll-to-roll type adhering device (not shown) to adhering the protective film 12 to the first main surface 11a of the transparent film substrate 11 while transporting the transparent film substrate 11.

[0060] Next, each layer of the laminate 10 will be described in detail.

[0061] (Transparent film 13) The transparent film 13 is, for example, a transparent resin film having flexibility. Examples of materials constituting the transparent film 13 include polyester resin, polyolefin resin, polystyrene resin, acrylic resin, polycarbonate resin, polyethersulfone resin, polysulfone resin, polyamide resin, polyimide resin, cellulose resin, norbornene resin, polyarylate resin, and polyvinyl alcohol resin. Examples of polyester resins include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of polyolefin resins include polyethylene, polypropylene, and cycloolefin polymer (COP). Examples of cellulose resins include triacetyl cellulose (TAC). These materials may be used alone or in combination of two or more. From the viewpoints of transparency and strength, the material of the transparent film 13 is preferably one selected from the group consisting of polyester resin, polyolefin resin, and cellulose resin, more preferably one selected from the group consisting of PET, COP, and TAC, and even more preferably TAC. In other words, as the transparent film 13, a type of film selected from the group consisting of polyester resin film, polyolefin resin film, and cellulose resin film is preferable, a type of film selected from the group consisting of PET film, COP film, and TAC film is more preferable, and a TAC film is even more preferable.

[0062] From the viewpoint of strength, the transparent film 13 has a thickness of preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. From the viewpoint of handleability, the transparent film 13 has a thickness of preferably 300 μm or less, and more preferably 200 μm or less.

[0063] One or both main surfaces of the transparent film 13 may be subjected to a surface modification treatment. Examples of the surface modification treatment include corona treatment, plasma treatment, ozone treatment, primer treatment, glow treatment, and coupling agent treatment.

[0064] From the viewpoint of improving the transparency of the antireflection film, the transparent film 13 has a total light transmittance (JIS K 7375-2008) of preferably 80% or more, more preferably 90% or more, and even more preferably 95% or more and 100% or less.

[0065] (Hard Coat Layer 14) The hard coat layer 14 is a layer that enhances mechanical properties such as hardness and elastic modulus of the anti-reflection film. The hard coat layer 14 is made of, for example, a cured product of a curable resin composition (composition for forming a hard coat layer). Examples of the curable resin contained in the curable resin composition include polyester resin, acrylic resin, urethane resin, urethane acrylate resin, amide resin, silicone resin, epoxy resin, and melamine resin. These curable resins may be used alone or in combination of two or more kinds. From the viewpoint of enhancing the hardness of the hard coat layer 14, the curable resin is preferably one or more kinds selected from the group consisting of acrylic resin and urethane acrylate resin, and more preferably urethane acrylate resin.

[0066] In addition, examples of the curable resin composition include an ultraviolet-curable resin composition and a thermosetting resin composition. From the viewpoint of improving the productivity of the anti-reflection film, the curable resin composition is preferably an ultraviolet-curable resin composition. The ultraviolet-curable resin composition includes one or more selected from the group consisting of an ultraviolet-curable monomer, an ultraviolet-curable oligomer, and an ultraviolet-curable polymer. A specific example of the ultraviolet-curable resin composition includes a hard coat layer forming composition described in JP 2016-179686 A.

[0067] The curable resin composition may also contain particles having a number-average primary particle diameter of 0.5 μm or more (hereinafter, sometimes referred to as "microparticles"). That is, the hard coat layer 14 may contain microparticles. By blending microparticles in the curable resin composition, it is possible to adjust the hardness, surface roughness, refractive index, and antiglare properties of the hard coat layer 14. Examples of the microparticles include metal (or semi-metal) oxide particles, glass particles, and organic particles. Examples of materials for the metal (or semi-metal) oxide particles include silica, alumina, titania, zirconia, calcium oxide, tin oxide, indium oxide, cadmium oxide, and antimony oxide. Examples of materials for the organic particles include polymethyl methacrylate, polystyrene, polyurethane, acrylic-styrene copolymer, benzoguanamine, melamine, and polycarbonate.

[0068] In order to easily adjust the antiglare properties of the hard coat layer 14, the number average primary particle diameter of the microparticles is preferably 1.0 μm or more and 5.0 μm or less, and more preferably 2.0 μm or more and 4.0 μm or less.

[0069] In order to easily adjust the antiglare property of the hard coat layer 14, the amount of the microparticles in the hard coat layer 14 is preferably 5 parts by weight or more, and may be 10 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more, relative to 100 parts by weight of the curable resin. The upper limit of the amount of the microparticles in the hard coat layer 14 is, for example, 90 parts by weight, preferably 80 parts by weight, and may be 70 parts by weight, relative to 100 parts by weight of the curable resin.

[0070] The curable resin composition may contain particles having a number-average primary particle diameter of less than 0.5 μm (hereinafter, may be referred to as "nanoparticles"). When the hard coat layer 14 is made of a cured product of the curable resin composition containing nanoparticles, fine irregularities are formed on the surface of the hard coat layer 14, and the adhesion between the hard coat layer 14 and the layer formed thereon tends to be improved.

[0071] From the viewpoint of forming a fine uneven shape that contributes to improving adhesion, the number average primary particle diameter of the nanoparticles is preferably 20 nm or more and 80 nm or less, more preferably 25 nm or more and 70 nm or less, and even more preferably 30 nm or more and 60 nm or less.

[0072] As the material of the nanoparticles, inorganic oxides are preferred. Examples of inorganic oxides include oxides of metals (or semi-metals) such as silicon oxide (silica), titanium oxide, aluminum oxide, zirconium oxide, niobium oxide, zinc oxide, tin oxide, cerium oxide, and magnesium oxide. The inorganic oxide may be a composite oxide of a plurality of (semi-)metals. Among the inorganic oxides exemplified above, silicon oxide is preferred because of its high effect of improving adhesion. In other words, as the nanoparticles, silicon oxide particles (silica particles) are preferred. Functional groups such as acrylic groups and epoxy groups may be introduced to the surfaces of inorganic oxide particles as nanoparticles in order to improve adhesion and affinity with resins.

[0073] The amount of nanoparticles in the hard coat layer 14 is preferably 5 parts by weight or more, and may be 10 parts by weight or more, 20 parts by weight or more, or 30 parts by weight or more, relative to 100 parts by weight of the curable resin. If the amount of nanoparticles is 5 parts by weight or more, it is possible to further improve the adhesion with the layer formed on the hard coat layer 14. The upper limit of the amount of nanoparticles in the hard coat layer 14 is, for example, 90 parts by weight, preferably 80 parts by weight, and may be 70 parts by weight, relative to 100 parts by weight of the curable resin.

[0074] The curable resin composition (hard coat layer forming composition) contains, for example, the above-mentioned curable resin and a polymerization initiator (for example, a photopolymerization initiator), and if necessary, a solvent capable of dissolving or dispersing these components. In addition to the above-mentioned components, the curable resin composition (hard coat layer forming composition) may contain additives such as microparticles, nanoparticles, leveling agents, viscosity adjusters (thixotropic agents, thickeners, etc.), antistatic agents, antiblocking agents, dispersants, dispersion stabilizers, antioxidants, ultraviolet absorbers, antifoaming agents, surfactants, and lubricants.

[0075] The thickness of the hard coat layer 14 is preferably 1 μm or more, more preferably 2 μm or more, from the viewpoint of increasing the hardness of the hard coat layer 14. The thickness of the hard coat layer 14 is preferably 50 μm or less, more preferably 40 μm or less, even more preferably 35 μm or less, and even more preferably 30 μm or less, from the viewpoint of ensuring the flexibility of the antireflection film.

[0076] (Method of forming hard coat layer 14) The hard coat layer 14 is formed, for example, by applying a curable resin composition (composition for forming a hard coat layer) to one main surface of the transparent film 13 (first main surface 13a of the transparent film 13 in FIG. 1), and removing the solvent and curing the resin as necessary. By providing the hard coat layer 14 on one main surface of the transparent film 13, a transparent film substrate 11 including the transparent film 13 and the hard coat layer 14 is obtained as shown in FIG.

[0077] The coating method of the hard coat layer forming composition may be any suitable method such as bar coating, roll coating, gravure coating, rod coating, slot orifice coating, curtain coating, fountain coating, comma coating, etc. The drying temperature of the coating film after coating may be set to an appropriate temperature depending on the composition of the hard coat layer forming composition, for example, 50°C or higher and 150°C or lower. When the resin component in the hard coat layer forming composition is a thermosetting resin, the coating film is cured by heating. When the resin component in the hard coat layer forming composition is a photocurable resin, the coating film is cured by irradiating it with active energy rays such as ultraviolet rays. The integrated light amount of the irradiated light is preferably 100 mJ / cm. 2 More than 500mJ / cm 2 The following is the result.

[0078] In order to improve the adhesion between the hard coat layer 14 and a layer formed thereon, the main surface of the hard coat layer 14 opposite to the transparent film 13 (in FIG. 1, the second main surface 11b of the transparent film substrate 11) may be bombarded. The gas used for the bombardment is preferably at least one selected from the group consisting of rare gases (specifically, argon gas, etc.) and oxygen gas.

[0079] In order to further increase the adhesion between the hard coat layer 14 and the layer formed thereon, it is preferable to bombard the main surface of the hard coat layer 14 opposite the transparent film 13 under a pressure condition of 0.1 Pa or more and 1.0 Pa or less.

[0080] In order to further increase the adhesion between the hard coat layer 14 and the layer formed thereon, the effective power density in the bombardment process is set to 0.01 W·min / cm 2 ·m or more, and 0.02W·min / cm 2 m or more, and 0.03 W min / cm 2 In order to suppress deformation of the transparent film substrate during the bombardment treatment process, the effective power density during the bombardment treatment process is preferably 0.60 W min / cm or more.2 ·m or less, and 0.55W·min / cm 2 m or less, and 0.50 W min / cm 2 It is more preferable that the effective power density is equal to or less than 1.0 W / cm. 2 ) divided by the film transport speed (m / min) in the roll-to-roll system. Even if the plasma output is the same, if the transport speed is high, the effective treatment power will decrease.

[0081] (Base material layer 15) The substrate layer 15 is formed of, for example, any suitable film. Examples of the material of the film include polyester resins such as polyethylene terephthalate resins, polycycloolefin resins such as polynorbornene resins, polyolefin resins such as polypropylene, polyamide resins, polycarbonate resins, and copolymer resins thereof. In order to increase the hardness of the substrate layer 15, polyester resins are preferred as the material of the substrate. The thickness of the substrate layer 15 is, for example, 10 μm or more and 200 μm or less, and preferably 20 μm or more and 150 μm or less. The substrate layer 15 may be a laminate of two or more layers.

[0082] (adhesive layer 16) The adhesive layer 16 is formed of, for example, any appropriate adhesive (pressure-sensitive adhesive). Examples of the adhesive include (meth)acrylic adhesives, urethane adhesives, and silicone adhesives. The thickness of the adhesive layer 16 is, for example, 1 μm or more and 20 μm or less, and preferably 2 μm or more and 10 μm or less.

[0083] In order to improve the transportability of the laminate 10, the total thickness of the base layer 15 and the adhesive layer 16 (the thickness of the protective film 12) is preferably 15 μm or more and 150 μm or less, and more preferably 20 μm or more and 100 μm or less.

[0084] [Anti-reflection layer formation process and in-line measurement process] Next, the antireflection layer forming step and the in-line measurement step will be described with reference to Fig. 2 and Figs. 3A to C. Fig. 2 is a schematic diagram showing an example of a film forming apparatus for the antireflection layer. Figs. 3A to C are cross-sectional views showing steps of an example of the antireflection layer forming step.

[0085] First, an example of a film forming apparatus for anti-reflection layers will be described. The film forming apparatus shown in FIG. 2 is a film forming apparatus that can continuously perform the anti-reflection layer forming process and the in-line measurement process while transporting the laminate in one direction, and can reflect the detection results in the in-line measurement process in the film forming conditions of the anti-reflection layer forming process. The film forming apparatus shown in FIG. 2 includes a first film forming roll 281 and a second film forming roll 282. Four film forming chambers (a first film forming chamber 210, a second film forming chamber 220, a third film forming chamber 230, and a fourth film forming chamber 240) separated by partitions are provided along the circumferential direction of each of the film forming rolls 281 and 282. A cathode is provided in each film forming chamber, and the cathodes 214, 224, 234, and 244 are connected to power sources 216, 226, 236, and 246, respectively. Targets 213, 223, 233 and 243 are disposed on the cathodes 214, 224, 234 and 244, respectively, so as to face the film-forming rolls 281 and 282. Gas inlet pipes are connected to the film-forming chambers 210, 220, 230 and 240, and valves 219, 229, 239 and 249 are provided upstream of the gas inlet pipes.

[0086] A roll of the laminate 10 (see FIG. 3A) is set on an unwinding roll 251 in the preparation chamber 250. The laminate 10 unwound from the unwinding roll 251 is transported onto a first film-forming roll 281 and is led in sequence to the first film-forming chamber 210 and the second film-forming chamber 220. In the first film-forming chamber 210, a high refractive index layer 102 is formed on the side of the hard coat layer 14 opposite to the transparent film 13 side (in FIG. 3A, the second main surface 11b of the transparent film substrate 11), and in the second film-forming chamber 220, a low refractive index layer 103 is formed on the high refractive index layer 102 (see FIG. 3B). The laminate 10 on which the high refractive index layer 102 and the low refractive index layer 103 are formed is transported onto the second film-forming roll 282, and the high refractive index layer 104 and the low refractive index layer 105 are sequentially formed in the third film-forming chamber 230 and the fourth film-forming chamber 240 (see FIG. 3C). Details of the high refractive index layer and the low refractive index layer will be described later. By the above antireflection layer forming process, the antireflection layer 101 having the high refractive index layer 102, the low refractive index layer 103, the high refractive index layer 104 and the low refractive index layer 105 in this order is formed on the second main surface 11b of the transparent film substrate 11, and the antireflection film 100 (laminate structure) shown in FIG. 3C is obtained.

[0087] The antireflection film 100 on which the antireflection layer 101 has been formed is introduced into a winding chamber 260 and wound up by a winding roll 261, thereby obtaining a roll of the antireflection film 100.

[0088] In the winding chamber 260, a light irradiation section 291 and a light detection section 293 are arranged so as to face the antireflection layer 101 of the antireflection film 100. In addition, a light irradiation section 294 and a light detection section 295 are arranged downstream of the light irradiation section 291 and the light detection section 293 so as to face each other across the antireflection film 100. In the in-line measurement process, the reflected light of the light irradiated from the light irradiation section 291 to the antireflection layer 101 is detected by the light detection section 293, and then the transmitted light of the light irradiated from the light irradiation section 294 to the antireflection layer 101 is detected by the light detection section 295. The light irradiated from the light irradiation section 291 and the light irradiation section 294 may be white light or monochromatic light as long as it contains visible light. The light irradiation may be continuous or intermittent.

[0089] The reflected light detected by the light detection unit 293 and the transmitted light detected by the light detection unit 295 are converted into electrical signals by light receiving elements (not shown), and calculations are performed by a calculation unit (not shown) as necessary. The calculation unit calculates the spectrum of the detected reflected light and transmitted light, and calculates the color of a specific color system (for example, the XYZ color system, L * a * b * The image is converted into a color system (e.g., color coordinate system) or the film thickness is calculated.

[0090] Furthermore, the calculation unit determines the difference between the reflection characteristics of the detected reflected light and the desired reflected light characteristics, and also determines the difference between the transmission characteristics of the detected transmitted light and the desired transmitted light characteristics. If the difference exceeds a threshold, the calculation unit transmits a signal to the control unit 275 to change the deposition conditions for the thin film. The control unit 275 adjusts the deposition conditions for the antireflection layer 101 so that the characteristics of the reflected light (reflectance, hue, etc.) and the characteristics of the transmitted light (spectral shape, etc.) fall within a predetermined range.

[0091] Examples of the film forming conditions to be adjusted include the amount of gas introduced into the film forming chamber, the film transport speed, and the amount of power input. For example, in the film forming apparatus shown in FIG. 2, the control unit 275 adjusts the rotation speeds of the unwinding roll 251, the winding roll 261, the first film forming roll 281, and the second film forming roll 282, the amount of power input to the power sources 216, 226, 236, and 246, and the openings of the valves 219, 229, 239, and 249 of the gas introduction pipes, thereby adjusting the film forming conditions of the thin film in each film forming chamber. For example, the change in the characteristics of the reflected light is mainly caused by the variation in the film thickness of the thin film. Therefore, it is preferable to adjust the film forming conditions of the thin film so that the film thickness of the thin film formed in each film forming chamber approaches the set value. In addition, the change in the characteristics of the transmitted light is mainly caused by the coloring of the thin film. Therefore, it is preferable to adjust the film forming conditions of the thin film so that the coloring of the thin film formed in each film forming chamber is suppressed. The adjustment of the film forming conditions is performed, for example, by PID control.

[0092] In order to determine the difference between the target reflected light characteristics and transmitted light characteristics, it is necessary to determine the reference reflected light characteristics and transmitted light characteristics in advance. The reference reflected light characteristics and transmitted light characteristics are appropriately determined according to the product specifications, etc. Examples include a method of using the center of the product's specification range as the reference, and a method of using the reflected light spectrum calculated by optical calculation from the set film thickness and refractive index of each layer (see the examples in JP 2016-122173 A) as the reference. In addition, the reflected light spectrum and transmitted light spectrum of the product measured offline may be used as the reference.

[0093] As described above, this manufacturing method can improve the detection accuracy of reflected light and transmitted light in in-line inspection, making it possible to easily keep the reflected light characteristics and transmitted light characteristics of the anti-reflection film within an acceptable range.

[0094] In order to suppress the variation in the reflected light characteristics in the width direction of the anti-reflection film, it is preferable to provide a plurality of light irradiating units 291 and light detecting units 293 in the width direction of the anti-reflection layer 101, and perform in-line reflected light measurement (irradiation of visible light and detection of reflected light) at a plurality of positions in the width direction of the anti-reflection layer 101. Similarly, in order to suppress the variation in the transmitted light characteristics in the width direction of the anti-reflection film, it is preferable to provide a plurality of light irradiating units 294 and light detecting units 295 in the width direction of the anti-reflection layer 101, and perform in-line transmitted light measurement (irradiation of visible light and detection of transmitted light) at a plurality of positions in the width direction of the anti-reflection layer 101. In this case, for example, if a plurality of gas introduction pipes are provided in the width direction of the film in each film forming chamber, it becomes possible to individually adjust the amount of gas introduced at a plurality of positions in the width direction of the film.

[0095] When forming the anti-reflection layer 101 by a reactive sputtering method, it is preferable to control the amount of reactive gas such as oxygen gas introduced by plasma emission monitoring (PEM) control when adjusting the film formation conditions of the anti-reflection layer 101. In the PEM control, the plasma emission intensity of the sputtering film formation is detected, and the amount of reactive gas introduced is adjusted so that the emission intensity becomes a predetermined control value (set point, hereinafter sometimes referred to as "SP"). By automatically adjusting the amount of gas introduced so that the plasma emission intensity is constant, it is possible to maintain the transition region and form a film at a high rate, and also to keep the film formation rate constant. However, when film formation is performed continuously for a long period of time, the film formation rate changes even if the plasma emission intensity is the same due to the influence of erosion of the target, etc. Therefore, in order to suppress the fluctuation of the reflection light characteristics and transmission light characteristics in the longitudinal direction of the anti-reflection film when performing continuous film formation for a long period of time, it is preferable to appropriately adjust the SP of the PEM based on the measurement results of the optical characteristics in the in-line measurement process.

[0096] In the PEM control, in order to control the state of sputtering in each deposition chamber, the plasma emission intensity is constantly monitored by the PEM, and the amount of gas introduced into each deposition chamber is feedback-controlled based on the SP of the emission intensity set within a predetermined range. By providing a plurality of PEMs in the width direction of the film, it is possible to set the SP individually for each PEM. This allows the balance of the amount of gas introduced into the width direction position corresponding to the PEM to be adjusted, so that the anti-reflection layer 101 having a uniform thickness in the width direction can be formed. For example, the reflected light is detected in an in-line measurement process, the film thickness is calculated from the detection result, and the SP is changed according to the calculation result so that the film thickness of the anti-reflection layer 101 is uniform in the length direction or width direction of the film, thereby maintaining the reflection light characteristics in the length direction or width direction of the film uniform.

[0097] In general, when forming an anti-reflective layer by reactive sputtering, it is difficult to stably maintain the transition region, and therefore the anti-reflective layer is prone to coloring. As described above, the present manufacturing method can improve the detection accuracy of transmitted light, and therefore the transmitted light characteristics of the anti-reflective layer can be easily kept within an allowable range. Therefore, according to the present manufacturing method, even if reactive sputtering is adopted, the transmitted light characteristics of the anti-reflective layer can be easily kept within an allowable range, and therefore coloring of the anti-reflective layer can be suppressed.

[0098] This manufacturing method may further include, after the in-line measurement step, a step S4 of peeling off the protective film 12 from the transparent film substrate 11. An optical layer such as a polarizing plate is laminated on the first main surface 11a of the transparent film substrate 11 after the protective film 12 is peeled off.

[0099] (Anti-reflection layer 101) Next, the antireflection layer 101 will be described in detail. The antireflection layer 101 is composed of two or more thin layers. The antireflection layer 101 shown in FIG. 3C has four layers, namely, a high refractive index layer 102, a low refractive index layer 103, a high refractive index layer 104, and a low refractive index layer 105, in this order from the hard coat layer 14 side. The antireflection layer of the antireflection film is not limited to a four-layer structure like the antireflection layer 101, and may be a two-layer structure, a three-layer structure, a five-layer structure, or a stacked structure of six or more layers. In order to reduce reflection at the air interface, it is preferable that the outermost layer (the layer farthest from the transparent film substrate) of the antireflection layer of the antireflection film is a low refractive index layer.

[0100] In general, the optical film thickness (product of refractive index and thickness) of the antireflection layer is adjusted so that the inverted phases of incident light and reflected light cancel each other out. By making the antireflection layer a multilayer laminate of two or more thin layers with different refractive indexes, the reflectance can be reduced over a wide wavelength range of visible light.

[0101] Examples of the thin film material constituting the antireflection layer 101 include metal (or semi-metal) oxides, nitrides, fluorides, etc. The antireflection layer 101 is preferably an alternating laminate of high refractive index layers and low refractive index layers, and more preferably an alternating laminate of two or more high refractive index layers and two or more low refractive index layers.

[0102] The high refractive index layer has a refractive index of, for example, 1.9 or more, preferably 2.0 or more. Examples of materials for the high refractive index layer include titanium oxide, niobium oxide (Nb2O5, etc.), zirconium oxide, tantalum oxide, zinc oxide, indium oxide, indium tin oxide (ITO), and antimony-doped tin oxide (ATO). Among these, at least one selected from the group consisting of titanium oxide and niobium oxide is preferred. The low refractive index layer has a refractive index of, for example, 1.6 or less, preferably 1.5 or less. Examples of materials for the low refractive index layer include silicon oxide (SiO2, etc.), titanium nitride, magnesium fluoride, barium fluoride, calcium fluoride, hafnium fluoride, and lanthanum fluoride. Among these, silicon oxide is preferred. In particular, it is preferred to alternately stack a niobium oxide thin film as the high refractive index layer and a silicon oxide thin film as the low refractive index layer. In addition to the low refractive index layer and the high refractive index layer, a medium refractive index layer having a refractive index of more than 1.6 and less than 1.9 may be provided.

[0103] The thickness of the high refractive index layer and the low refractive index layer is preferably 5 nm or more and 200 nm or less, and more preferably 10 nm or more and 150 nm or less. The thickness of each layer may be designed so that the reflectance of visible light is small according to the refractive index and the lamination structure. For example, the lamination structure of the high refractive index layer and the low refractive index layer may be a four-layer structure consisting of a high refractive index layer with an optical thickness of 20 nm or more and 55 nm or less, a low refractive index layer with an optical thickness of 35 nm or more and 60 nm or less, a high refractive index layer with an optical thickness of 65 nm or more and 250 nm or less, and a low refractive index layer with an optical thickness of 100 nm or more and 150 nm or less, from the transparent film substrate 11 side.

[0104] When the antireflection layer 101 is a four-layer alternating laminate in which niobium oxide thin films as high refractive index layers and silicon oxide thin films as low refractive index layers are alternately laminated, the antireflection layer 101 may be configured to have, from the hard coat layer 14 side, a niobium oxide thin film having a thickness of 5 nm to 20 nm, a silicon oxide thin film having a thickness of 20 nm to 60 nm, a niobium oxide thin film having a thickness of 25 nm to 120 nm, and a silicon oxide thin film having a thickness of 50 nm to 100 nm, in that order.

[0105] In order to obtain an antireflection film having excellent high-temperature durability, the thickness of the antireflection layer 101 is preferably 100 nm or more and 300 nm or less, more preferably 120 nm or more and 280 nm or less, even more preferably 140 nm or more and 260 nm or less, and even more preferably 160 nm or more and 240 nm or less. In this specification, the "thickness of the antireflection layer" refers to the sum of the thicknesses of the layers constituting the antireflection layer (total thickness).

[0106] The method for forming the anti-reflection layer 101 is not particularly limited, and may be either a wet coating method or a dry coating method. Since a thin film with a uniform thickness can be formed, dry coating methods such as vacuum deposition, CVD, and sputtering are preferred, and sputtering is more preferred. From the viewpoint of increasing productivity, the method for forming the anti-reflection layer 101 is preferably a method for forming a film using a roll-to-roll sputtering film-forming apparatus as shown in FIG. 2 (roll-to-roll sputtering method). In the sputtering method, film formation is performed while introducing an inert gas such as argon, and a reactive gas such as oxygen as necessary, into a film-forming chamber. When forming an oxide film by the sputtering method, either a method using an oxide target or a reactive sputtering method using a metal (or semimetal) target can be performed.

[0107] When an insulating oxide such as silicon oxide is formed using an oxide target, RF discharge is required, so that the film formation rate is low and the productivity tends to be low. Therefore, the sputtering of oxide is preferably performed by reactive sputtering using a metal target. In the reactive sputtering, the film is formed while introducing an inert gas such as argon and a reactive gas such as oxygen into the film formation chamber. In the reactive sputtering, it is preferable to adjust the amount of oxygen so that the film is a transition region between the metal region and the oxide region. When film formation is performed in a metal region where the amount of oxygen is insufficient, the amount of oxygen in the obtained oxide film becomes significantly smaller than the stoichiometric composition, and the oxide film tends to have a metallic luster and to decrease in transparency. In addition, in an oxide region where the amount of oxygen is large, the film formation rate tends to decrease extremely. By adjusting the amount of oxygen so that the sputtering film formation is in the transition region, the oxide film can be formed at a high rate. When the anti-reflective layer 101 is formed by reactive sputtering, the amount of reactive gas introduced can be controlled by the above-mentioned PEM control, so that the film formation conditions of the anti-reflective layer 101 can be adjusted more easily. The sputtering power source used in the reactive sputtering method is preferably a DC power source or an MFAC power source (an AC power source having a frequency band of several kHz to several MHz).

[0108] The power density when performing the sputtering method is, for example, 0.1 W / cm 2 More than 20W / cm 2 less than or equal to 1 W / cm 2 More than 15W / cm 2 The surface temperature of the film-forming roll when performing the sputtering method is, for example, from −25° C. to 25° C., and preferably from −20° C. to 0° C. The pressure in the film-forming chamber when performing the sputtering method is, for example, from 0.01 Pa to 10 Pa, and preferably from 0.1 Pa to 1.0 Pa.

[0109] The anti-reflection film obtained by the present production method is used in displays such as liquid crystal displays, organic EL displays, etc. In particular, when used as the outermost surface layer of a display, the visibility of the display is improved due to the anti-reflection effect.

[0110] [Preferable embodiment of the method for producing an anti-reflection film] In the present manufacturing method, in order to further improve the detection accuracy of reflected light and transmitted light in in-line inspection, it is preferable to satisfy the following condition 1, more preferably to satisfy the following condition 2, and even more preferably to satisfy the following condition 3. Condition 1: The surface haze value of the rear surface of the protective film is 6.0% or more and 50.0% or less, and the root-mean-square slope Sdq of the rear surface of the protective film is 0.10 or more and 0.50 or less. Condition 2: The above condition 1 is satisfied, and the surface haze value of the back surface of the protective film minus the surface haze value of the adhesive surface of the protective film is 5.0% or more. Condition 3: The above condition 2 is satisfied, and the root mean square slope Sdq of the back surface of the protective film minus the root mean square slope Sdq of the adhesive surface of the protective film is 0.05 or more.

[0111] [Other embodiments] Although the manufacturing method of the anti-reflection film according to the present embodiment has been described above, the present invention is not limited to the above-mentioned embodiment. For example, the in-line measurement process may be performed at any stage after at least one thin film layer is formed. For example, after the high refractive index layer 102 and the low refractive index layer 103 are formed on the first film-forming roll 281, the light irradiation unit 297 (see FIG. 2) irradiates the low refractive index layer 103 with visible light, and the reflected light is detected by the light detection unit 299 (see FIG. 2), thereby performing in-line detection of the reflected light. In addition, after the high refractive index layer 102 and the low refractive index layer 103 are formed on the first film-forming roll 281, the light irradiation unit (not shown) irradiates the low refractive index layer 103 with visible light, and the transmitted light is detected by the light detection unit (not shown), thereby performing in-line detection of the transmitted light.

[0112] 2 shows an example in which the reflected light is detected and then the transmitted light is detected, but in the present invention, the transmitted light may be detected and then the reflected light may be detected. Also, the reflected light and the transmitted light may be detected simultaneously.

[0113] In addition, in-line detection may be performed at two or more locations. For example, after forming the high refractive index layer 102 and the low refractive index layer 103, in-line detection of reflected light and transmitted light may be performed, and further, after forming the high refractive index layer 104 and the low refractive index layer 105, in-line detection of reflected light and transmitted light may be performed. In this way, by performing in-line measurement at two or more locations, it becomes easier to determine the deposition chamber in which the deposition conditions should be adjusted, and more precise control becomes possible.

[0114] The manufacturing method of the present invention may further include a step S5 of forming a primer layer on one main surface (second main surface) of the transparent film substrate before the antireflection layer forming step. When the manufacturing method of the present invention further includes step S5, the antireflection layer is formed on the main surface of the primer layer opposite to the transparent film substrate in the antireflection layer forming step.

[0115] By providing a primer layer, the adhesion between the transparent film substrate and the anti-reflection layer is increased. Examples of materials for the primer layer include metals (or semi-metals) such as silicon, nickel, chromium, tin, gold, silver, platinum, zinc, titanium, indium, tungsten, aluminum, zirconium, and palladium; alloys of these metals (or semi-metals); and oxides, fluorides, sulfides, and nitrides of these metals (or semi-metals). The oxide constituting the primer layer may be a composite oxide such as indium tin oxide (ITO). Among these, inorganic oxides are preferred as materials for the primer layer, with silicon oxide, indium oxide, or ITO being more preferred, and SiOx (x<2) being even more preferred.

[0116] In order to ensure the light transmittance of the primer layer while increasing the adhesion between the transparent film substrate and the antireflection layer, the thickness of the primer layer is preferably 0.5 nm or more and 20 nm or less, more preferably 0.5 nm or more and 10 nm or less, and even more preferably 1.0 nm or more and 10 nm or less.

[0117] The method for forming the primer layer is not particularly limited, and may be either a wet coating method or a dry coating method. Since a thin film with a uniform thickness can be formed, a dry coating method such as a vacuum deposition method, a CVD method, or a sputtering method is preferable, and a sputtering method is more preferable. From the viewpoint of increasing productivity, a method for forming the primer layer using a roll-to-roll sputtering film forming device (roll-to-roll sputtering method) is preferable. In the roll-to-roll sputtering method, for example, the primer layer and the anti-reflection layer can be continuously formed while transporting a long laminate in the longitudinal direction (MD direction). When forming the primer layer by the sputtering method, for example, the film forming conditions can be appropriately set among the conditions exemplified in the description of the anti-reflection layer 101 above.

[0118] The method for producing an anti-reflection film according to the present invention may further include a step of forming an anti-soiling layer after the in-line measurement step. The material of the anti-soiling layer is preferably a fluorine-containing compound.

[0119] In the method for producing an anti-reflection film according to the present invention, the protective film may be composed of only one layer (substrate layer). In the protective film composed of only the substrate layer, for example, one of the main surfaces has adhesiveness. EXAMPLES

[0120] Examples of laminates that can be used in the present invention and examples of producing anti-reflection films using these laminates will be described below.

[0121] <Preparation of Laminate> [Preparing the protective film] Protective films P1 to P7 shown in Table 1 were prepared as protective films for producing a laminate. Protective film P1 was composed only of a base layer (thickness: 28 μm) having adhesive properties on one main surface. Protective films P2 to P7 all had a base layer and an adhesive layer. Protective films P5 to P7 had an adhesive layer which was a light-diffusing adhesive layer containing particles, and the particle content in the light-diffusing adhesive layer was different from one another.

[0122] [Table 1]

[0123] [Formation of hard coat layer] 100 parts by weight of ultraviolet-curable urethane acrylate monomer (refractive index: 1.51), 14 parts by weight of polystyrene beads (refractive index: 1.59, number-average primary particle diameter: 3.5 μm), 5 parts by weight of alkylphenone photopolymerization initiator, 135 parts by weight of toluene, and 10 parts by weight of ethyl acetate were mixed to prepare a composition for forming a hard coat layer with a solid content concentration of 45% by weight. Next, the composition for forming a hard coat layer was applied to one main surface of a TAC film (thickness: 40 μm, refractive index: 1.49) as a transparent film to form a coating film. Next, the coating film was dried by heating at a temperature of 80° C. for 2 minutes, and then cured by ultraviolet irradiation. As a result, an antiglare hard coat layer (a hard coat layer having an uneven surface structure) with a thickness of 7 μm was formed on one main surface of the TAC film, and a transparent film substrate was obtained.

[0124] [Attaching protective film] The TAC film side of the main surface of the transparent film substrate obtained by the above procedure was attached to the adhesive surface of the above-mentioned protective film (specifically, any of the protective films P1 to P7) to obtain a laminate. Hereinafter, the laminate obtained using the protective film P1 may be referred to as "laminate L1". Similarly, the laminates obtained using the protective films P2, P3, P4, P5, P6, and P7 may be referred to as "laminates L2, L3, L4, L5, L6, and L7", respectively.

[0125] <Preparation of anti-reflection film> The methods for producing the antireflection films of Production Examples 1 to 3 and Comparative Production Examples 1 to 4 will be described below.

[0126] [Production Example 1] (Bombardment) The roll-to-roll plasma processing equipment achieves a pressure of 0.6 Pa and an effective power density of 0.34 W·min / cm 2 The laminate L1 was transported under the condition of 1000 rpm and 1000 m, and the main surface of the hard coat layer of the laminate L1 (specifically, the main surface of the hard coat layer opposite the TAC film side) was bombarded. During the bombardment, argon gas (flow rate: 1050 sccm) was introduced into the apparatus.

[0127] Next, the primer layer forming process and the anti-reflection layer forming process will be described. In the primer layer forming process and the anti-reflection layer forming process, when forming the oxide film, the film was formed while introducing argon gas and oxygen gas into the film forming chamber. When forming the oxide film, the pressure was kept constant by adjusting the amount of argon gas introduced and exhausted, and the amount of oxygen gas introduced was adjusted by plasma emission monitoring (PEM) control so that the film formation mode was maintained in the transition region.

[0128] (Primer layer formation process) The laminate L1 after the bombardment process was introduced into a roll-to-roll sputtering deposition apparatus, and the deposition chamber was filled with 1×10 -4 The pressure was reduced to 10 Pa. Next, while transporting the laminate L1, the surface temperature of the film-forming roll was set to -8°C, and a SiOx layer (x<2) having a thickness of 3.5 nm was formed (deposited) as a primer layer on the main surface of the hard coat layer opposite the TAC film side by reactive sputtering. A Si target was used as the target material for forming the primer layer. In addition, when depositing the film by reactive sputtering, the power source was set to an MFAC power source (frequency: 40 kHz), and the power density was set to 3 W / cm. 2 The pressure in the film formation chamber was set to 0.4 Pa.

[0129] (Anti-reflection layer formation process) Following the formation of the primer layer, a roll-to-roll sputtering deposition apparatus was used to transport the laminate L1 after the formation of the primer layer, while a reactive sputtering method was used to deposit a first layer: a niobium oxide layer having a thickness of 12 nm (refractive index: 2.33), a second layer: a silicon oxide layer having a thickness of 28 nm (refractive index: 1.46), a third layer: a niobium oxide layer having a thickness of 100 nm, and a fourth layer: a silicon oxide layer having a thickness of 85 nm, in this order, on the main surface of the primer layer opposite to the hard coat layer side. As a result, an antireflection layer having a four-layer structure (a four-layer structure consisting of a first layer, a second layer, a third layer, and a fourth layer) was formed on one main surface of the primer layer, and an antireflection film of Production Example 1 was obtained. In addition, in the deposition of each of the first layer to the fourth layer, the surface temperature of the deposition roll was set to -8°C, and the power source was an MFAC power source (frequency: 40 kHz). In addition, in the deposition of the first layer and the third layer, a Nb target was used, and the power density was 13 W / cm 2 The pressure in the deposition chamber was set to 0.5 Pa. In addition, in the deposition of the second and fourth layers, a Si target was used and the power density was 8 W / cm. 2 The pressure in the film formation chamber was set to 0.5 Pa.

[0130] [Production Example 2, Production Example 3 and Comparative Production Examples 1 to 4] Antireflection films of Production Example 2, Production Example 3 and Comparative Production Examples 1 to 4 were obtained in the same manner as in Example 1, except that Laminates L2 to L7 were used instead of Laminate L1, respectively.

[0131] <Internal haze measurement> [Measurement of internal haze value of protective films P1 to P4] First, the adhesive surface of a protective film (specifically, any of the protective films P1 to P4) was attached to one main surface of a 1.3 mm thick slide glass via an acrylic adhesive layer (thickness: 23 μm), and then a PET film (thickness: 38 μm) was attached to the back surface of the protective film via an acrylic adhesive layer (thickness: 23 μm) to obtain a laminate La. Separately, a laminate Lb having a layer structure of slide glass (thickness 1.3 mm) / acrylic adhesive layer (thickness: 46 μm) / PET film (thickness: 38 μm) was obtained using the same materials as the slide glass, acrylic adhesive layer, and PET film used in forming the laminate La. Next, the haze values ​​of the laminates La and Lb were measured using a haze meter ("HZ-2" manufactured by Suga Test Instruments Co., Ltd.) according to the method described in JIS K7136-2000. The internal haze value of the protective films P1 to P4 was determined by subtracting the haze value of the laminate Lb from the haze value of the laminate La. When measuring the haze values ​​of the laminates La and Lb, light was irradiated from the PET film side.

[0132] [Measurement of internal haze value of protective films P5 to P7] First, the adhesive surface of a protective film (specifically, any of the protective films P5 to P7) was attached to one main surface of a slide glass having a thickness of 1.3 mm, and then a PET film (thickness: 38 μm) was attached to the back surface of the protective film via an acrylic adhesive layer (thickness: 23 μm) to obtain a laminate Lc. Separately, a laminate Ld having a layer structure of slide glass (thickness 1.3 mm) / acrylic adhesive layer (thickness: 23 μm) / PET film (thickness: 38 μm) was obtained using the same materials as the slide glass, acrylic adhesive layer, and PET film used in forming the laminate Lc. Next, the haze values ​​of the laminate Lc and the laminate Ld were measured using a haze meter (manufactured by Suga Test Instruments Co., Ltd., "HZ-2") according to the method described in JIS K7136-2000. The value obtained by subtracting the haze value of the laminate Ld from the haze value of the laminate Lc was taken as the internal haze value of the protective films P5 to P7. When measuring the haze value of the laminates Lc and Ld, light was irradiated from the PET film side.

[0133] <Measurement of surface haze value> [Measurement of the surface haze value on the back side of protective films P1 to P4] First, a laminate Le having a layer structure of a slide glass (thickness 1.3 mm) / acrylic adhesive layer (thickness: 23 μm) / protective film (specifically, any of the protective films P1 to P4) was obtained using the same materials as the slide glass and the acrylic adhesive layer used in forming the laminate La. When forming the laminate Le, the adhesive surface of the protective film was attached to the acrylic adhesive layer. Next, the haze value of the laminate Le was measured using a haze meter ("HZ-2" manufactured by Suga Test Instruments Co., Ltd.) according to the method described in JIS K7136-2000. The value obtained by subtracting the internal haze value of the protective film (specifically, any of the protective films P1 to P4) from the haze value of the laminate Le was taken as the surface haze value of the back surface of the protective films P1 to P4. When measuring the haze value of the laminate Le, light was irradiated from the protective film side.

[0134] [Measurement of surface haze value of adhesive surfaces of protective films P1 to P4] First, a laminate Lf having a layer structure of slide glass (thickness 1.3 mm) / acrylic adhesive layer (thickness: 23 μm) / protective film (specifically, any of the protective films P1 to P4) was obtained using the same materials as the slide glass and the acrylic adhesive layer used in forming the laminate La. When forming the laminate Lf, the back side of the protective film was attached to the acrylic adhesive layer. Next, the haze value of the laminate Lf was measured using a haze meter ("HZ-2" manufactured by Suga Test Instruments Co., Ltd.) according to the method described in JIS K7136-2000. The value obtained by subtracting the internal haze value of the protective film (specifically, any of the protective films P1 to P4) from the haze value of the laminate Lf was taken as the surface haze value of the adhesive surface of the protective films P1 to P4. When measuring the haze value of the laminate Lf, light was irradiated from the protective film side.

[0135] [Measurement of the surface haze value on the back of protective films P5 to P7] First, the adhesive surface of a protective film (specifically, any of the protective films P5 to P7) was attached to a slide glass (thickness 1.3 mm) of the same type as the slide glass used in forming the laminate Lc to obtain a laminate Lg. Next, the haze value of the laminate Lg was measured using a haze meter ("HZ-2" manufactured by Suga Test Instruments Co., Ltd.) according to the method described in JIS K7136-2000. The value obtained by subtracting the internal haze value of the protective film (specifically, any of the protective films P5 to P7) from the haze value of the laminate Lg was taken as the surface haze value of the back surface of the protective films P5 to P7. When measuring the haze value of the laminate Lg, light was irradiated from the protective film side.

[0136] <Measurement of the surface shape of protective film> A protective film (more specifically, any of protective films P1 to P7) was used as a sample, and the three-dimensional surface shape of the surface of the protective film (more specifically, either the back surface or the adhesive surface) was measured under the following conditions using a shape analysis laser microscope (Keyence Corporation, "VK-X1000"), and the root-mean-square slope Sdq, arithmetic mean height Sa, and root-mean-square height Sq were obtained in accordance with ISO 25178. Observation magnification: 150x Measurement field of view: 50μm×50μm

[0137] <Measurement of rear surface reflectance of anti-reflection film> First, an anti-reflective film FS was prepared as a reference sample. In detail, when forming a laminate, an acrylic adhesive layer (thickness: 23 μm) and a black PET film (thickness: 50 μm, visible light transmittance: 0.1%) were sequentially laminated on the main surface of the transparent film substrate on the TAC film side instead of the protective film P1, and the anti-reflective film FS was prepared in the same manner as the anti-reflective film of Production Example 1. The layer structure of the anti-reflective film FS was black PET film / acrylic adhesive layer / TAC film / hard coat layer / primer layer / anti-reflective layer. Next, the anti-reflective film FS and the anti-reflective films to be measured (specifically, the anti-reflective films of Production Examples 1 to 3 and Comparative Production Examples 1 to 4) were irradiated with visible light (wavelength: 550 nm) from the anti-reflective layer side at an incident angle of 2° using an ultraviolet-visible-near infrared spectrophotometer (Hitachi High-Tech Corporation's "U4100"), and the reflectance (unit: %) of 2° regular reflection was measured. The value obtained by subtracting the reflectance of the antireflection film FS from the reflectance of the antireflection film to be measured (specifically, any of the antireflection films of Production Examples 1 to 3 and Comparative Production Examples 1 to 4) was taken as the back surface reflectance (unit: %) of the antireflection film to be measured. When the back surface reflectance was 0.30% or less, it was evaluated as "back surface reflection is reduced". On the other hand, when the back surface reflectance was more than 0.30%, it was evaluated as "back surface reflection is not reduced".

[0138] <Measurement of parallel light transmittance of anti-reflection film> For the anti-reflection films to be measured (specifically, the anti-reflection films of Production Examples 1 to 3 and Comparative Production Examples 1 to 4), the total light transmittance (unit: %) and the diffuse transmittance (unit: %) were measured by a haze meter ("HZ-2" manufactured by Suga Test Instruments Co., Ltd.) according to the method described in JIS K7105 (currently discontinued) (ISO 13468-2:1999) when light was irradiated from the anti-reflection layer side. The parallel ray transmittance (unit: %) of the anti-reflection film to be measured was calculated based on the formula "parallel ray transmittance = total light transmittance - diffuse transmittance". When the parallel ray transmittance was 30.0% or more, it was evaluated as "high parallel ray transmittance". On the other hand, when the parallel ray transmittance was less than 30.0%, it was evaluated as "not high parallel ray transmittance".

[0139] <Result> For the antireflection films of Production Examples 1 to 3 and Comparative Production Examples 1 to 4, the type of protective film used, the haze value of the protective film used, the surface shape of the protective film used, the back reflectance, and the parallel ray transmittance are shown in Table 2. In Table 2, "-" means that no measurement was performed.

[0140] [Table 2]

[0141] As shown in Table 2, the internal haze value of the protective film was 4.0% or less in Production Examples 1 to 3. The surface haze value of the back surface of the protective film was 6.0% or more and 50.0% or less in Production Examples 1 to 3. The root mean square slope Sdq of the back surface of the protective film was 0.10 or more and 0.50 or less in Production Examples 1 to 3.

[0142] As shown in Table 2, in Production Examples 1 to 3, the back surface reflectance was 0.30% or less. Thus, the back surface reflection was reduced in Production Examples 1 to 3. In Production Examples 1 to 3, the parallel ray transmittance was 30.0% or more. Thus, the parallel ray transmittance was high in Production Examples 1 to 3.

[0143] As shown in Table 2, the internal haze value of the protective film exceeded 4.0% in Comparative Production Examples 1 to 4. The surface haze value of the rear surface of the protective film exceeded 50.0% in Comparative Production Example 1. In Comparative Production Examples 2 to 4, the root mean square slope Sdq of the rear surface of the protective film was less than 0.10.

[0144] As shown in Table 2, in Comparative Production Examples 1 to 3, the back surface reflectance exceeded 0.30%. Therefore, the back surface reflection was not reduced in Comparative Production Examples 1 to 3. In Comparative Production Examples 1, 3, and 4, the parallel ray transmittance was less than 30.0%. Therefore, in Comparative Production Examples 1, 3, and 4, the parallel ray transmittance was not high.

[0145] The above results demonstrate that the present invention can provide a method for producing an anti-reflection film that can improve the detection accuracy of reflected light and transmitted light in in-line inspection. [Explanation of symbols]

[0146] 10: Laminate 11: Transparent film base 12: Protective film 13: Transparent film 14: Hard coat layer 100:Anti-reflective film 101: Anti-reflection layer

Claims

1. A step S1 of preparing a laminate having a transparent film substrate and a protective film peelably attached to a first main surface side of the transparent film substrate; A step S2 of forming an anti-reflection layer consisting of two or more thin films on the second main surface side of the transparent film substrate; and a step S3 of depositing at least one layer constituting the anti-reflection layer, irradiating the layer with visible light, and detecting reflected light and transmitted light, The steps S2 and S3 are continuously performed while the laminate is transported in one direction, The internal haze value of the protective film is 4.0% or less, The method for producing an antireflection film, wherein the surface haze value of the main surface of the protective film opposite to the transparent film substrate side is 6.0% or more and 50.0% or less.

2. The method for producing an anti-reflection film according to claim 1 , wherein the surface haze value of the main surface of the protective film opposite the transparent film substrate side minus the surface haze value of the main surface of the protective film facing the transparent film substrate side is 5.0% or more.

3. A step S1 of preparing a laminate having a transparent film substrate and a protective film peelably attached to a first main surface side of the transparent film substrate; A step S2 of forming an anti-reflection layer consisting of two or more thin films on the second main surface side of the transparent film substrate; and a step S3 of depositing at least one layer constituting the anti-reflection layer, irradiating the layer with visible light, and detecting reflected light and transmitted light, The steps S2 and S3 are continuously performed while the laminate is transported in one direction, The internal haze value of the protective film is 4.0% or less, The method for producing an antireflection film, wherein the root mean square slope Sdq of the main surface of the protective film opposite to the transparent film substrate is 0.10 or more and 0.50 or less.

4. The method for producing an anti-reflection film according to claim 3, wherein the root-mean-square slope Sdq of the main surface of the protective film opposite the transparent film substrate side minus the root-mean-square slope Sdq of the main surface of the protective film facing the transparent film substrate side is 0.05 or more.

5. The method for producing an antireflection film according to claim 1 or 3, wherein in the step S2, the antireflection layer is formed by a reactive sputtering method.

6. 4. The method for producing an antireflection film according to claim 1, wherein in the step S3, after all layers constituting the antireflection layer are formed, the antireflection layer is irradiated with visible light, and the reflected light and transmitted light are detected.

7. The method for producing an antireflection film according to claim 1 , wherein a deposition condition of the antireflection layer in the step S2 is adjusted according to a result of detection of the reflected light and the transmitted light in the step S3 .

8. The method for producing an anti-reflection film according to claim 1 , further comprising, after step S3 , a step S4 of peeling off the protective film from the transparent film substrate.

9. The transparent film substrate includes a transparent film and a hard coat layer provided on a first main surface side of the transparent film, The method for producing an anti-reflection film according to claim 1 , wherein in the laminate, the protective film is attached to a second main surface side of the transparent film.

10. The method further includes a step S5 of forming a primer layer on the second main surface side of the transparent film substrate before the step S2, The method for producing an antireflection film according to claim 1 or 3, wherein in the step S2, the antireflection layer is formed on a main surface of the primer layer opposite to the transparent film substrate.

Citation Information

Patent Citations

  • Measurement of reflectivity of plastic film

    JP1996082600A

  • Production of antireflection film

    JP1996082701A

  • Method of continuous film deposition using atmospheric pressure plasma

    JP2001181850A

  • Atmospheric pressure plasma discharge thin film-forming process, optical film, anti-reflection film, and image display device

    JP2003183836A

  • Antireflection film and method for manufacturing the same, and method for measuring reflected light characteristics of antireflection film

    JP2016122173A

Cited By

  • Information processing system, information processing method, and information processing program

    JP7838721B2

  • JPWO2025210977A1